2003
DOI: 10.1007/s005950300080
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Retropharyngeal Hematoma of a Parathyroid Cyst: Report of a Case

Abstract: A 41-year-old woman presented with severe and sudden anterior neck swelling, pain, and dysphagia. Computed tomography (CT) scan and ultrasound of the neck showed a giant mass in the retropharyngeal space, displacing the trachea and esophagus anteriorly. Aspiration cytology was done, following which extensive cervical and chest ecchymosis occurred and her symptoms immediately improved. A repeat CT scan demonstrated that the cervical giant mass had vanished, but there was a residual mass in the left paratracheal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Such cysts may occasionally cause compressive symptoms such as dysphagia, dyspnoea, hoarseness or pain, especially when localized in the mediastinum [12][13][14]. Cases complicated by massive haemorrhage into the cervical tissue and the mediastinum have also been reported [15][16][17], but these hematomas are more usually related to the cystic degeneration of an adenoma than with a true non-functional cyst.…”
Section: Discussionmentioning
confidence: 98%
“…Such cysts may occasionally cause compressive symptoms such as dysphagia, dyspnoea, hoarseness or pain, especially when localized in the mediastinum [12][13][14]. Cases complicated by massive haemorrhage into the cervical tissue and the mediastinum have also been reported [15][16][17], but these hematomas are more usually related to the cystic degeneration of an adenoma than with a true non-functional cyst.…”
Section: Discussionmentioning
confidence: 98%
“…Despite typical pathologic findings of parathyroid adenoma, the PTH was within normal limits (1, 2, 6, 8). …”
Section: Discussionmentioning
confidence: 87%
“…Cervical hematoma presents as acute painful swelling and bruising of neck, and this is associated with dyspnea, hoarseness and dysphagia caused by compression on the surrounding organs such as the trachea, esophagus and recurrent laryngeal nerve (2, 4, 5). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last 80 years, approximately 20 cases of acute hemorrhage resulting from the spontaneous rupture of the parathyroid glands have been reported in the English literature. A previous study reported that the causes of these hemorrhages include parathyroid glands that are enlarged by adenomas, [1][2][3][4][5][6][7][8][9] primary or secondary hyperplasia, [10][11][12] cysts [13][14][15] and carcinomas. 16) Some authors report that blood supplies may occasionally fail to meet the increased demands caused by these lesions.…”
Section: Discussionmentioning
confidence: 99%